2019
DOI: 10.1016/j.foodchem.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Whey protein isolate modulates beta-carotene bioaccessibility depending on gastro-intestinal digestion conditions

Abstract: Carotenoids are lipophilic phytochemicals; their intake has been associated with reduced chronic diseases. However, their absorption depends on emulsification during digestion and incorporation into mixed micelles, requiring digestive enzymes, gastric peristalsis, bile, and dietary lipids. In this study, we investigated whether whey-protein-isolate (WPI), a commonly consumed protein source, can modulate β-carotene bioaccessibility in vitro, especially under incomplete digestive conditions, i.e. under low diges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 38 publications
(55 reference statements)
0
33
0
6
Order By: Relevance
“…Some authors have investigated the dietary potential of these compounds and the potential influence of a number of host‐related factors on bioavailability‐related properties such as bioaccessibility and absorbability (Bohn et al., 2017). Others have found dietary lipids to considerably enhance carotenoid absorption by fostering micellization (Iddir et al., 2019). As regards safety, the European Food Safety Authority (EFSA) has set a maximum daily βC intake of 15 mg for safe consumption (EFSA, 2012; Meléndez‐Martínez, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have investigated the dietary potential of these compounds and the potential influence of a number of host‐related factors on bioavailability‐related properties such as bioaccessibility and absorbability (Bohn et al., 2017). Others have found dietary lipids to considerably enhance carotenoid absorption by fostering micellization (Iddir et al., 2019). As regards safety, the European Food Safety Authority (EFSA) has set a maximum daily βC intake of 15 mg for safe consumption (EFSA, 2012; Meléndez‐Martínez, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Only then will β-carotene be available to travel to the target tissues and organs where it can exert beneficial health effects. For ingested β-carotene, there are several limitations that limits the amount that is distributed in the systemic circulation in its native form-e.g., chemical instability during the digestion process, poor solubility in the gastrointestinal tract (GIT), slow uptake from the GIT, cleavage by BCO1 in the enterocyte (producing 2 retinal molecules) [53], and first-pass metabolism ( Figure 1). The oral bioavailability (F) of encapsulated β-carotene in delivery systems can be determined by the following equation:…”
Section: Release Of β-Carotene From the Food Matrixmentioning
confidence: 99%
“…Rich and team recorded a one-hour increased transfer to oil in case of in vitro digested digesta at pH 2.1 as compared to in vitro digested digesta at pH 6.2 [64]. However, it has also been reported that under some conditions, proteins can aid in the emulsification of carotenoids including β-carotene in the digesta, improving its transfer into lipid droplet and thus later intestinal bioaccessibility [53]. This seemed to be the case especially under marginal digestion conditions-i.e., under low enzymatic digestive activity.…”
Section: Mass Transfer To Oil Phasementioning
confidence: 99%
“…For ingested β-carotene, there are several limitations, which limits the proportion that arrives in the systemic circulation in its native form, e.g. chemical instability during the digestion process, poor solubility in the gastrointestinal tract (GIT), slow uptake from the GIT, cleavage by BCO1 in the enterocyte (producing 2 molecules of retinal) [53], and first-pass metabolism (Figure 4). The oral bioavailability (F) of encapsulated β-carotene in delivery systems can be determined by the following equation F = F × F × F Here, FB is the fraction of consumed β-carotene that survived through the upper GIT and released from the food matrix/delivery system into the GIT, thus becoming bioaccessible for uptake by brush-bordered enterocytes.…”
Section: Bioaccessibility =mentioning
confidence: 99%
“…Rich and team recorded a one-hour increase transfer to oil in case of in vitro digested digesta at pH 2.1 as compared to in vitro digested digesta at pH 6.2 [64]. However, it has also been reported that under some conditions, proteins can aid in the emulsification of carotenoids including β-carotene in the digesta, improving its transfer into lipid droplet and thus later intestinal bioaccessibility [53]. This seemed to be the case especially under marginal digestion conditions, i.e.…”
Section: Mass Transfer To Oil Phasementioning
confidence: 99%